China’s Belt and Road Initiative: Understanding the dynamics of a global transformation - CHAY, Yue Wah (Institutional Knowledge at Singapore Management University, 2019)
This book presents critical analyses of China's Belt-Road-Initiative (BRI) from economic, social, political and geographical perspectives. Contributed by academics and business professionals from Asia, Europe and Australia, the chapters offer readers a range of regional viewpoints and insights into China's grand development strategy — primarily aimed at boosting connectivity across Asia and beyond via investments in infrastructural projects. The chapters also discuss the contemporary economic, financial, political and infrastructural developments related to the BRI and the challenges that confront the Initiative.This edited volume serves as a primer to China's mega strategic undertaking, a supplementary companion and reference resource to those familiar with the BRI.